2017
DOI: 10.1039/c6md00563b
|View full text |Cite
|
Sign up to set email alerts
|

Novel bivalent securinine mimetics as topoisomerase I inhibitors

Abstract: A series of novel bivalent securinine mimetics incorporating different linkers between C-15 and C-15′ were synthesized and their topoisomerase I (Topo I) inhibitory activities evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Letter / Cluster / New Tools Template for SYNLETT Thieme approval of the ADC drug, Mylotarg Ⓡ (gemtuzumab ozogamicin), 14 ADCs have received market approval so far worldwide. 7 Importantly, the payloads of all of these drugs have their origins in natural product structures.…”
Section: Synlettmentioning
confidence: 99%
See 1 more Smart Citation
“…Letter / Cluster / New Tools Template for SYNLETT Thieme approval of the ADC drug, Mylotarg Ⓡ (gemtuzumab ozogamicin), 14 ADCs have received market approval so far worldwide. 7 Importantly, the payloads of all of these drugs have their origins in natural product structures.…”
Section: Synlettmentioning
confidence: 99%
“…12 Even though a few preliminary mechanistic studies regarding the bioactivities of these alkaloids have been reported, the exact targets for the majority of these bioactivities have yet to be identified. Notably, Chen and co-workers reported that securinine derivatives effectively inhibit DNA topoisomerase I (Topo I), 13,14 the target of the FDA-approved ADC drug Enhertu (trastuzumab deruxtecan). 15 From a structural perspective, basic monomeric securinega alkaloids are characterized by a fused tetracyclic core with a conjugated ester moiety and a piperidine heterocycle.…”
mentioning
confidence: 99%
“…As a result of these studies, an effective and promising inhibitor of Topoisomerase 1 was identied: a bivalent securinine mimetic with a rigid linker (compound R2 ( 80)). 92 Challenging securinine dimers with high antitumor activity are described in the patent 94 (Fig. 8).…”
Section: Bivalent Securinine Analoguesmentioning
confidence: 99%
“…It is clear that the linker structure between two securinine molecules influences the activity of bivalent mimetics. The work 92 describes the synthesis of bivalent mimetics with rigid, semi-rigid, and flexible linkers between the C-15 and C-15′ atoms. The design strategy for bivalent mimetics with different linkers is shown in Fig.…”
Section: Bivalent Securinine Analoguesmentioning
confidence: 99%
See 1 more Smart Citation